Elucidation of the Flavonoid Catabolism Pathway in Pseudomonas putida PML2 by Comparative Metabolic Profiling - Pillai, Bhinu V. S. (American Society for Microbiology, 2002)
Flavonoids are 15-carbon plant secondary metabolites exuded in the rhizosphere that hosts several flavonoid-degrading bacteria. We studied flavonoid catabolism in a plant growth-promoting rhizobacterial strain of Pseudomonas by using a combination of biochemical and genetic approaches. Transposants carrying mini-Tn5gfp insertions were screened for flavonoid auxotrophy, and these mutant strains were found to be unable to grow in the flavonols naringenin and quercetin, while their growth in glycerol was comparable to that of the parental strain. In order to understand flavonoid catabolism, culture supernatants, whole-cell fractions, cell lysate, and cell debris of the wild-type and mutant strains were analyzed. Intermediates that accumulated intracellularly and those secreted in the medium were identified by a combination of reversed-phase high-pressure liquid chromatography and electrospray ionization-mass spectrometry. Structures of four key intermediates were confirmed by one-dimensional nuclear magnetic resonance spectroscopy. Comparative metabolic profiling of the compounds in the wild-type and mutant strains allowed us to understand the degradation events and to identify six metabolic intermediates. The first step in the pathway involves 3,3′-didehydroxylation, followed by hydrolysis and cleavage of the C-ring, leading via subsequent oxidations to the formation of protocatechuate. This is the first report on quercetin dehydroxylation in aerobic conditions leading to naringenin accumulation.